Exploring the behavioural and purchase intentions of Specialty Coffee consumers in Pretoria - Lemmer, Catherine (The IIE, 2022)
Specialty Coffee is a prominent and emerging market globally, and in recent years it has affixed itself in the South African coffee industry (Coffee Business Intelligence South Africa, 2021). Specialty Coffee is described as quality coffee differentiated by sustainable and ethical production, intricate bean roasting and expert bean brewing. Creating a distinct flavourful experience for consumers to enjoy (Famous Bean, 2021). Despite the increasing prominence of Specialty Coffee in South Africa, limited research has been conducted on the consumer behaviours, behavioural intentions and purchase intentions of Specialty Coffee consumers in South Africa (Urwin, 2019). Resultantly, this paper explores the variables influencing Specialty Coffee consumers located in Pretoria, Gauteng, behavioural intentions and ultimate purchase intentions. This has been done to expand knowledge on Specialty Coffee consumers, and their consumer behaviour to enable local Specialty Coffee businesses to differentiate themselves in the competitive market. Further, Specialty Coffee brands can better meet the needs and expectations of their consumers, expanding the local Specialty Coffee market (van der Merwe & Maree, 2016 ). The research conducted in this paper utilised Azjen’s (1991) Theory of Planned Behaviour (TPB), to explore the behavioural intentions and purchase intentions of Specialty Coffee consumers in Pretoria. It was identified that attitude and perceived behaviour control (TPB) plays the most influential role in driving consumer behaviour to purchase intention (Ajzen, 1991).
Keywords: Consumer behaviour; Buying behavior; Attitude; Coffee culture; Purchase intentions